'The Lord': An Apology for the Muslim Faith from the Island of Soqotra1. (23rd August 2019) - Ad-Da'rhi, Issa Gum'an; Kogan, Leonid; Cherkashin, Dmitry
Abstract: The present study is a unique witness of the nascent literacy in the Modern South Arabian language Soqotri (Island Soqotra, Gulf of Aden, Yemen). For the first time, a consciously created, non-traditional specimen of Soqotri narrative appears both in the newly designed Arabic-based Soqotri script and the standard Semitological transcription, along with an English translation and philological annotations. The motivation behind the creation of this piece is, strikingly, neither artistic nor scientific, but religious, which opens new avenues for the development of the Soqotri language in complex framework of todays Arab and Islamic world: contrary to the widespread belief, Soqotri is not necessarily bound to the transmission of the traditional oral lore, but can serve as an efficient vehicle for creating and publishing texts pertaining to the vital interests of todays islanders.